2017
DOI: 10.1071/wf16166
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating a reluctance to simplify: exploring the radio communication context in wildland firefighting

Abstract: Although communication is often cited as a contributor to organisational accidents, complexities of the communication context are still understudied. In training materials and some investigative reports, communication is often presented as an equipment issue or as a simple skill that can be picked up on the job. However, interviews with operational and managerial professionals in wildland firefighting reveal 10 simplifications in guidance about radio communication that do not match the complexities experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, this tendency sometimes occurred without making a proper assessment of whether the more complex discarded ideas would have been better to meet the requirements of the task at hand. In this vein, Fox et al (2017) showed that simplifications in communication may be counterproductive to match the complexities of the task. Mutual trust was found to be a critical aspect to generate a positive work atmosphere in the multidisciplinary teams, as highlighted by Maier et al (2008).…”
Section: Effect Of Team Disciplinary Composition On Design Teamwork Q...mentioning
confidence: 99%
“…However, this tendency sometimes occurred without making a proper assessment of whether the more complex discarded ideas would have been better to meet the requirements of the task at hand. In this vein, Fox et al (2017) showed that simplifications in communication may be counterproductive to match the complexities of the task. Mutual trust was found to be a critical aspect to generate a positive work atmosphere in the multidisciplinary teams, as highlighted by Maier et al (2008).…”
Section: Effect Of Team Disciplinary Composition On Design Teamwork Q...mentioning
confidence: 99%
“…However, this tendency occasionally occurred without making a proper assessment of whether the more complex discarded ideas would have been better to meet the requirements of the task at hand. In this vein, Fox et al (2017) showed that simplifications in communication may be counterproductive to matching the complexities of the task.…”
Section: Effect Of Team Disciplinary Composition On Design Teamwork Q...mentioning
confidence: 99%